Why are online games so self‐involving: A social identity analysis of massively multiplayer online role‐playing games. (20th March 2015) - Guegan, Jérôme; Moliner, Pascal; Buisine, Stéphanie
Abstract: This article investigates the ways in which players of massively multiplayer online role‐playing games (MMORPGs) internalize being a player into their self‐concept. In accordance with the social identity framework, we assume that being a player and being a member of a guild within the game can both shape the social identity of members. In two studies, we survey players inside or outside the MMORPG. Players are interviewed either at an interguild comparison level or at the more inclusive level of MMORPG players. Study 1 (n = 84) reveals favoritism for the in‐group guild in a within‐game context, and Study 2 (n = 200) shows that valuation of and identification with the in‐group are moderated by the interview context and the level of category inclusion: Inside the game, the guild is more valued and identification is emphasized. In contrast, valuation of and identification with MMORPG players is not influenced by the interview context. Together, by examining both valuation and identification processes, this research reveals that playing online games may be self‐involving because being a player, but also being a member of a guild, directly contribute to the social identity. Copyright © 2015 John Wiley & Sons, Ltd.